Optimization of the organic solar cells for high performance - Chen, Honghua (Nanyang Technological University, 2022)
This work focuses on the device structure and operation principle of organic solar cells(OSC). The properties and effects on the device performance of the electrodes, substrates, modified layers and active layers of OSC have been investigated. This work, Poly(3-hexylthiophene) (P3HT) was chosen as the absorber of the solar cell, which has the advantage of better electronic transmission performance. Simultaneously, Phenyl-C61-butyric acid methyl ester (PCBM) was extensively studied as the electron acceptor in the active layer, because of its better hole mobility. The Poly(3,4-ethylenedioxythiophene) (PEDOT) was coated on the IndiumTinOxide (ITO) film, and the Polystyrene sulfonates (PSS) film was used as the anode buffer layer.